The great ice race - Melendez, Renee; Aikins, Dave; Random House Children's Books; Viacom International (New York Random House, 2017)
"Blaze and his Monster Machine friends transform into race cars for a chance to win a wintry race! But troublesome Crusher will do anything to win--even cheat! Can Nickelodeon's Blaze and the Monster Machines stay cool under pressure as Crusher tries to knock the friends off course? " --
At head of title: Nickelodeon Blaze and the monster machines
Preschool - grade 1
2
Keywords: Automobile racing -- Fiction; Automobile racing -- Juvenile fiction; Automobile racing; JUVENILE FICTION / Concepts; JUVENILE FICTION / Media Tie-In; JUVENILE FICTION / Transportation; Monster trucks -- Fiction; Monster trucks -- Juvenile fiction; Monster trucks; Automobile racing -- Fiction; Monster trucks -- Fiction; Automobiles, Racing -- Fiction; Automobiles, Racing -- Juvenile fiction; Automobile racing -- Fiction; Automobile racing -- Juvenile fiction; Fiction; Juvenile works; Readers (Elementary); Readers (Elementary); Readers (Publications); Readers (Publications); Early Reader; Readers (Publications.)